RACIAL DISCRIMINATION IN HIDDEN FIGURES (2016) - Purasih, Jela Milenina (Universitas Negeri Surabaya, 2023)
The problem of discrimination in communities that have less power is still a concerned issue that often occurs in everyday life. One kind of discrimination is racial discrimination which is unfair treatment due to differences in skin color. One of movies that tell about racial discrimination is Hidden Figure (2016) which illustrates about African-American women who work at NASA during the Space Race who work as a minor community in NASA and have strong barriers for everyday whenever they work or do their job desk in NASA. The purpose of this research is to analyze and discuss how is racial discrimination depicted in Hidden Figure (2016) and how female characters cope with racial discrimination in Hidden Figure (2016). This research used a qualitative approach. The data collection method in this research used observing the movie and capturing the important scenes in Hidden Figures (2016). This research used two main theories to support the research in analyzing and discussing the phenomenon, which is The Three Levels of Racism by Day (2016) and The Resistance Strategy by Shorter-Gooden (2004). Based on the analysis, it shows that the movie has all of the 3 levels of racism mentioned by Day (2016) which consists of Institutionalized Racism, Person Mediated Racism, and Internalized Racism. Also, the movie is depicted on how the female characters using external resources and specific strategy to coping with racial discrimination.